THE CORRELATION BETWEEN KNOWLEDGE AND ATTITUDE WITH COMPLIANCE OF FE TABLET CONSUMPTION IN ANEMIA OF THE THIRD TRIMESTER PREGNANT WOMEN - Dwi Kurnia Purnama Sari; Masrufah (International Journal of Midwifery Research, 2021)
Anemia in pregnancy increases the risk of miscarriage, premature birth, low birth weight, bleeding after delivery. Anemia can be prevented by consuming a balanced nutritious diet and giving 90 tablets of Fe during pregnancy. The purpose of this study was to determine whether there was a correlation between knowledge and attitude with adherence to Fe tablet consumption in pregnant women with anemia in the third trimester in the working area of ​​Merakurak Health Center. The research design used an observational analytic design with a cross-sectional approach. The sampling technique was simple random sampling. The population was 21 pregnant women with Third Trimester anemia in the working area of ​​the Merakurak Health Center and a sample of 20 people. The contingency coefficient test using SPSS 21 obtained a value of 0.036 (p<0.05) meaning there was a correlation between knowledge and compliance and the contingency coefficient test is 0.264 (p>0.05) meaning there was no correlation between attitude and compliance. So it was suggested for more intensive socialization and supervision by families with a control card for Fe tablet consumption in pregnant women with anemia in the third trimester.